Pengaruh Latihan Single Leg Speed Hop Terhadap Keterampilan Long Passing - Putra Renaldi Perdana Simanjorang; Apri Agus; Andri Gemaini (JURNAL STAMINA, 2022)
Lack of long passing skills of Supra Pacific football school players Lubuk Pakam, This research is an experimental study that aims to see the results of single leg speed hop exercises on the long passing skills of football school players bo1a Supra Pacific Lubuk Pakam. The free variable is the single leg speed hop (X) practice, while the bound variable is the long passing skill (Y). This type of research is a pseudo experiment. Supra Pacific football school player Lubuk Pakam as many as 40 people as a population. Withdrawal until taken purposive sampling technique that is the player who participated in the exercise. The samples taken by the researchers numbered 12 players of Supra Pacific football school Lubuk Pakam. The research instrument uses a long passing skill test. Ana1isis statistical data techniques using liliefors norm1ity test and t-test with a significant level of ɔ=0.05. The result of this study is that there is an influence of single leg speed hop training on the long passing skills of Supra Pacific Football School players Lubuk Pakam